INTERACTIVE CONDUCT OF GAMES IN EDUCATION OF PRESCHOOL CHILDREN - Maryambibi Djumaniyazovna Abdullayeva (Web of Journals Publishing, 2024)
In order to improve the quality of education, the article talks about the skills of using game technologies in the preschool education system.
Keywords: preschool education, education, quality, goal, task, skill, system, technology, pedagogy.